Three genera in the Ceratocystidaceae are the respective symbionts of three independent lineages of ambrosia beetles with large, complex mycangia. Issue 11 (November 2015) - Mayers, Chase G.; McNew, Douglas L.; Harrington, Thomas C.; Roeper, Richard A.; Fraedrich, Stephen W.; Biedermann, Peter H.W.; Castrillo, Louela A.; Reed, Sharon E.
Abstract: The genus Ambrosiella accommodates species of Ceratocystidaceae ( Microascales ) that are obligate, mutualistic symbionts of ambrosia beetles, but the genus appears to be polyphyletic and more diverse than previously recognized. In addition to Ambrosiella xylebori, Ambrosiella hartigii, Ambrosiella beaveri, and Ambrosiella roeperi, three new species of Ambrosiella are described from the ambrosia beetle tribe Xyleborini : Ambrosiella nakashimae sp. nov. from Xylosandrus amputatus, Ambrosiella batrae sp. nov. from Anisandrus sayi, and Ambrosiella grosmanniae sp. nov. from Xylosandrus germanus . The genus Meredithiella gen. nov. is created for symbionts of the tribe Corthylini, based on Meredithiella norrisii sp. nov. from Corthylus punctatissimus . The genus Phialophoropsis is resurrected to accommodate associates of the Xyloterini, including Phialophoropsis trypodendri from Trypodendron scabricollis and Phialophoropsis ferruginea comb. nov. from Trypodendron lineatum . Each of the ten named species was distinguished by ITS rDNA barcoding and morphology, and the ITS rDNA sequences of four other putative species were obtained with Ceratocystidaceae -specific primers and template DNA extracted from beetles or galleries. These results support the hypothesis that each ambrosia beetle species with large, complex mycangia carries its own fungal symbiont. Conidiophore morphology and phylogenetic analyses using 18S (SSU) rDNA and TEF1α DNA sequences suggest that these three fungal genera within the Ceratocystidaceae independently adapted to symbiosis with the three respective beetle tribes. In turn, the beetle genera with large, complex mycangia appear to have evolved from other genera in their respective tribes that have smaller, less selective mycangia and are associated with Raffaelea spp. ( Ophiostomatales ).